2022
DOI: 10.3389/fneur.2021.760518
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Brain β-Amyloid Load in Parkinson's Disease With Mild Cognitive Impairment: A PET/MRI Study

Abstract: BackgroundMild cognitive impairment in Parkinson's disease (PD-MCI) is associated with faster cognitive decline and conversion to dementia. There is uncertainty about the role of β-amyloid (Aβ) co-pathology and its contribution to the variability in PD-MCI profile and cognitive progression.ObjectiveTo study how presence of Aβ affects clinical and cognitive manifestations as well as regional brain volumes in PD-MCI.MethodsTwenty-five PD-MCI patients underwent simultaneous PET/3T-MRI with [18F]flutemetamol and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…While comparing β-amyloid load in the subgroup of PD-MCI vs. noPD-MCI, we failed to find any significant difference in all examined cortical and subcortical areas. Indeed, our findings are consistent with recent research that equally did not support an association between increased Aβ deposition and cognitive decline in PD ( 17 , 18 , 44 ). It is worth noting that we compared the two groups on averaged SUVs evaluating β-amyloid load as continuous variables, being the main aim of the present study to use amyloid PET measures as continuous features implementing machine learning models.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While comparing β-amyloid load in the subgroup of PD-MCI vs. noPD-MCI, we failed to find any significant difference in all examined cortical and subcortical areas. Indeed, our findings are consistent with recent research that equally did not support an association between increased Aβ deposition and cognitive decline in PD ( 17 , 18 , 44 ). It is worth noting that we compared the two groups on averaged SUVs evaluating β-amyloid load as continuous variables, being the main aim of the present study to use amyloid PET measures as continuous features implementing machine learning models.…”
Section: Discussionsupporting
confidence: 93%
“…Besides mental symptoms, a growing body of evidence indicates the association between cognitive decline and several gait and balance dysfunction, including the postural instability gait difficulty (PIGD) phenotype ( 7 , 8 ), freezing of gait (FOG) ( 9 11 ), and specific walking alterations, especially in dual-task conditions, on quantitative gait evaluations ( 12 16 ). In addition, although the evidence consistently suggests that low cerebrospinal fluid levels of amyloid-β42, a marker of Alzheimer's disease (AD), may predict future cognitive decline and PDD ( 5 ), to date, amyloid-β (Aβ) Positron Emission Tomography (PET) imaging studies have reported conflicting results ( 17 21 ), thus failing to consistently demonstrate an association between Aβ plaques deposition and cognitive dysfunction in PD. Of note, many cross-sectional studies showed a relationship between Aβ pathology and the PIGD subtype in PD ( 22 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aβ retention can also be present in a minority of PD patients [ 70 ]. A recent 3-year longitudinal study [ 71 ] found that PD patients with enlarged Basal Ganglia PVS (BG-PVS) at baseline had reduced CSF Aβ 42 and had lower Montreal cognitive assessment (MoCA) scores at follow-up compared to PD patients without enlarged BG-PVS.…”
Section: Glymphatic System and Parkinson’s Diseasementioning
confidence: 99%
“…A recent 3-year longitudinal study [ 71 ] found that PD patients with enlarged Basal Ganglia PVS (BG-PVS) at baseline had reduced CSF Aβ 42 and had lower Montreal cognitive assessment (MoCA) scores at follow-up compared to PD patients without enlarged BG-PVS. However, several studies have shown a low prevalence of Aβ with PD without dementia [ 72 ] and those with MCI [ 70 ]. In a study utilising Positron Emission Tomography (PET) imaging with [ 18 F]Florbetaben in a large cohort of PD subjects (ranging from PD patients with normal cognition to subjects with MCI to Parkinson’s Disease Dementia), increasing age was associated with increased cortical [ 18 F]Florbetaben retention in the PD group.…”
Section: Glymphatic System and Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation